2x-6x+5=-3x-6+7

Simple and best practice solution for 2x-6x+5=-3x-6+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-6x+5=-3x-6+7 equation:



2x-6x+5=-3x-6+7
We move all terms to the left:
2x-6x+5-(-3x-6+7)=0
We add all the numbers together, and all the variables
2x-6x-(-3x+1)+5=0
We add all the numbers together, and all the variables
-4x-(-3x+1)+5=0
We get rid of parentheses
-4x+3x-1+5=0
We add all the numbers together, and all the variables
-1x+4=0
We move all terms containing x to the left, all other terms to the right
-x=-4
x=-4/-1
x=+4

See similar equations:

| 3x-14x=2341 | | 3x+91x=2123x | | -5x+8=3x-8 | | x+59+43=180 | | (2x-24)+(x-2)=x | | 1.5b=15 | | 6n−3=57 | | 7x-5=10x+7 | | 2y^2+6y-360=0 | | (2x-24)+(x-2)+x=180 | | 3x+4+2=7x-2 | | 2x+(21-2x)=21 | | 35x-5=12 | | 429÷3x=13 | | 6s=–8+5s | | –5w=–6w+10 | | 5x–4(x–3)=8 | | x=x+(3x+25)+(x-5)=180 | | 180=x+(3x+25)+(x-5)x= | | 180=x+3x+25+x-5 | | 180=x+(3x+25)+(x-5) | | x=(3x+35)x-5 | | y=34y-19 | | 15x/13-14x=15 | | X=34y-19 | | H=300-15t | | 3(2+x)-2(x-1)=7 | | CxC+C=210 | | 18n+150=402 | | (-8x+91)+(-4x+48)=2(x-6) | | 28-6=n | | 28+6=n |

Equations solver categories